Chirurgická léčba zlomenin talu--střednědobé funkční a rentgenové výsledky - Kopp, L; Obruba, P; Riegl, J; Meluzinová, P; Edelmann, K (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2013)
PURPOSE OF THE STUDY: The aim of this prospective study was to present injury characteristics and to evaluate therapeutic procedures and midterm functional and radiographic results of the surgical management of talus fractures. MATERIAL AND METHODS: In the period from January 1, 2004, to December 31, 2009, a total of 53 patients with 56 talar bone fractures or peritalar dislocations were treated surgically. The prospective study included 39 patients with 42 fractures of the talar neck and body; of these, 31 men had 34 fractures (79.5%) and eight women had eight fractures (20.5%). There were recorded demographic data, medical history, associated injuries, polytrauma criteria, time to surgery and its type, failure of osteosynthesis, complications associated with soft tissue healing, length of hospital stay, duration of follow-up, radiographic evidence of bone healing and the presence of avascular necrosis or arthritis. Fractures were classified according to the systems of Hawkins (modified by Canale), Sneppen and Marti. Outcomes were assessed on the basis of functional and radiographic scores (West Point Ankle Score). The injuries included 21 (50%) talar neck fractures, 12 (28.5%) isolated fractures of the talar body and nine (21.5%) combined fractures of the talar neck and body. There were four (9.5%) open fractures. Twenty-five (64.1%) patients had associated skeletal injuries; eight (20.5%) patients suffered polytrauma. Staged treatment was used in five patients (12.8%). The average time to final surgery was 4.2 days. The technique of minimally invasive osteosynthesis under fluoroscopic or arthroscopic control was used in 18 (42.9%) fractures, and open reduction and internal fixation was carried out in 24 (57.1%) fractures. The average follow-up was 30.9 months. RESULTS: Signs of avascular necrosis partly or completely affecting the talar body were found in six fractures (14.3%), three of which required secondary arthrodesis. Arthritis developed in 10 cases (23.8%) Functional and radiographic results assessed with the West Point Ankle Score, regardless of fracture type, were excellent in 17 (43.5%), good in 11 (28.2%), satisfactory in five (12.8%) and poor in six (15.5%) patients. DISCUSSION: High incidence of polytrauma and complex injuries of the hindfoot makes the timing of surgical management difficult and also affects its outcome. Timing used in our study is in agreement with general trends of staged talus fracture treatment. In accordance with the international practice, the majority of non-displaced talar neck fractures (Hawkins 1) were treated by means of osteosynthesis. We preferred minimally invasive fracture reduction under arthroscopic control in less complicated fracture types of the talar neck and body. The incidence of avascular necrosis, as reported in the literature, has had a decreasing tendency. Incidence of avascular necrosis without talar dome collapse does not necessarily lead to functional impairment. The results of functional and radiographic scoring were in agreement with the literature data and confirmed that functional outcome is related to the severity of fracture. CONCLUSIONS: Our results confirmed that the management of talar fractures by means of osteosynthesis is indicated even in nondisplaced Hawkins type 1 fractures, staged treatment is effective in dislocated and open fractures, delayed surgery is a safe procedure for less dislocated fractures and injuries requiring complex care should be referred to foot surgery centres.
Keywords: Adolescent; Adult; Fractures, Bone; Male; lidé; lidé středního věku; Humans; Fracture Fixation, Internal; vnitřní fixace fraktury; Middle Aged; Radiography; Young Adult; radiografie; mužské pohlaví; Talus; dospělí; talus; mladý dospělý; ženské pohlaví; mladiství; Female; fraktury kostí